2019
DOI: 10.1186/s12885-019-6424-4
|View full text |Cite
|
Sign up to set email alerts
|

Predicting prognosis according to preoperative chemotherapy response in patients with locally advanced lower rectal cancer

Abstract: BackgroundNeoadjuvant chemoradiotherapy is regarded as the standard of treatment for locally advanced lower rectal cancer, although some of these cases are systemic, and distant control may be inadequate. Neoadjuvant chemotherapy could compensate for such shortcomings, potentially yielding better survival outcomes. We aimed to stratify patients into prognostic groups on the basis of preoperative factors, including response to neoadjuvant chemotherapy.MethodsWe retrospectively analyzed patients with locally adv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 30 publications
0
18
0
2
Order By: Relevance
“…This evaluation can be performed within days to weeks of the start of the intervention and prior to surgery by assessing volume effects using RECIST criteria with CT or MRI [4,5], MRI based tumour regression grading [6], and mapping macroscopic and microscopic details about tumour architecture [7,8]. Results of prospective trials showed clinical complete response (cCR) or TNM down-staging after CRT is a biomarker of more favourable oncological outcomes in LARC [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…This evaluation can be performed within days to weeks of the start of the intervention and prior to surgery by assessing volume effects using RECIST criteria with CT or MRI [4,5], MRI based tumour regression grading [6], and mapping macroscopic and microscopic details about tumour architecture [7,8]. Results of prospective trials showed clinical complete response (cCR) or TNM down-staging after CRT is a biomarker of more favourable oncological outcomes in LARC [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, patients with SD/PD to IC showed that the tumor volume shrank insignificantly or rather increased. Several studies demonstrated the prognostic value of changes in the tumor volume in different types of cancers [ 24 , 25 ]. Therefore, the prognostic value of tumor response to IC in LANPC patients can be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…In other cancer sites, such as rectal cancer, the extent of tumor volume shrinkage is an established prognostic factor. [17] , [18] In small cell lung cancer, response volume also correlated to outcome of de nitive RT. [19] In locally advanved nasopharyngeal cancer, a study found a cutoff point (12.6%) of tumor volume reduction rate after neoadjuvant chemotherpay to serve as a prognositc value for disease control, including overall survival.…”
Section: Cut-off Point Of Tvrr-t For Os and Dsfmentioning
confidence: 99%